Protective Effect of Aloe Vera Gel Extract on Histopathologic Changes in Ovaries and Gonadotropin in MS Model of Rat (Bangladesh Journal of Medical Science, 2020)
Objective: Multiple sclerosis (MS) is a self-immune demyelinating disorder of the CNS, followed by neuropathic discomfort, especially in young people in reproductive age. So, This research was conducted with the aim of assessing the protective effect of Aloe vera gel (AVG) extract on histopathologic changes of the ovary and gonadotropin in an experimental MS model of rat.Methods: In this research, 30 pieces of rats of Wistar race were randomly divided into 6 groups of 5. 20 pieces, 14μl of ethidium bromide was injected in their lateral ventricles to induce MS. In 5 pieces as control group 2, 14μL of saline was injected into the lateral ventricles, and the remaining 5 rats were considered as control group 1. Treatment of three groups of rats with MS was performed with AVG extract at 50 mg/kg BW, 100 mg/kg BW 100 and 200 mg/ kg BW. At the end, blood sampling to measure serum FSH and LH, Their ovaries were isolated for microscopic examination.Results: The results of counting the number of ovarian follicles showed a significant decrease in the number of primary and secondary and graafian follicles in group 3, compared to the control group. There is a significant increase in the concentration of FSH and LH in group 3 in comparison to the control group.Conclusion: Finally, It can be said that by inducing MS, The number of ovarian follicles decreased, and the number of atretic follicles and the concentration of gonadotropin hormones increased, and treatment with AVG extract was effective in improving these factors.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.444-452